National Hispanic Democratic Caucus Reception at Miles, Sears and Eanni - Watkins, Howard::::::::: (1988)
Patience Milrod shaking hands with Attorney General John Van de Kamp; in background: Cindy Calvert, Municipal Court Judge Armando Rodriguez, ?